Land Surface Temperature Sensitivity to Changes in Vegetation Phenology Over Northern Deciduous Forests - Park, Chang-Eui; Jeong, Sujong (AMER GEOPHYSICAL UNION, 2023)
Changes in vegetation phenology are important contributors to seasonal climate change over the northern land surface. However, the biogeophysical effects of phenological shifts on land surface temperature (LST) remain uncertain. Here, we demonstrated the sensitivity of LST to advanced start of growing season (SOS) and delayed end of growing season (EOS) during corresponding green-up and senescence periods over northern deciduous forests. Moreover, the mechanism responsible for LST sensitivity was assessed by quantifying the contributions of biogeophysical properties to LST sensitivity by applying a two resistance mechanism method to an experimental set using Community Land Model version 5. LST sensitivities to advanced SOS and delayed EOS were -2.1 x 10-2 K day-1 and -2.8 x 10-2 K day-1, respectively, indicating cooling effects by phenological shifts. The different responses of the aerodynamic resistance to SOS and EOS could explain the higher LST sensitivity to EOS than that to SOS. The decrease in the aerodynamic resistance in response to delayed EOS was three times larger than that to advanced SOS, thereby inducing a larger surface cooling effect during senescence period through enhanced turbulent heat transfer. Thus, the reduced aerodynamic resistance could explain the cooling effect of the phenological shift, which is an important consideration for projecting seasonal climate change. The impact of phenological shifts in northern forests on land surface temperature (LST) is important for their potential to mitigate anthropogenic global warming due to increases in atmospheric greenhouse gases concentrations. In this study, biogeophysical impacts on LST were quantified based on analytic evaluation and model simulations. The findings indicated a cooling effect of -2.1 x 10-2 K day-1 and -2.8 x 10-2 K day-1 due to the advanced start of growing season and delayed end of growing season, respectively. These cooling effects are mostly caused by an enhancement in turbulent heat transfer from land to atmosphere through a decrease in aerodynamic resistance. Our results suggest reasons for the biogeophysical cooling effect of the lengthened growing season, which is important for projecting seasonal climate change. Biogeophysical impact of changes in vegetation phenology on land surface temperature over northern deciduous forest is examinedAdvance start of growing season and delayed end of growing season both induce land surface coolingThe mechanism responsible for surface cooling is enhanced turbulent heat transfer by a decrease in aerodynamic resistance